Rancang Bangun Pemantauan Pakan Ayam Otomatis Berbasis Internet Of Things (IOT). - Zikri Pradana; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Internet of Things (IoT) has become a separate of field of research since the development of internet technology and other communication media. Internet of Things allows humans to communicate with all devices connected to the internet network. One of the implementation Internet of Things is chicken feed monitoring. In this research will using Loadcell sensor, NodeMCu as a microcontroller and servo motor as an automatic open and close controller. ESP8266 which is already embedded in NodeMCu as a WI-FI module is used to connecting arduino to the internet. The results obtained from this monitoring is if chicken feed is less than 1kg, the servo will open to fill the chicken feed container. Conversely, if the chicken feed is fully loaded 10kg, the servo will be closed again. Keyword: Android, Internet of Things (IoT), monitoring, automatic, chicken feed.